Research on VPN service for government and enterprise customers in SDN-based vCPE networks - Fengchao FU; Peng WANG; Yuanbao XIE (Dianxin kexue)
SDN technology has been studied widely recently. The main idea of SDN-based vCPE is using custom hardware and software to replace CPE. All vCPEs are managed by the SDN controller in a centralized way and the open programmable north interface can be provided. In this way, not only a wealth of value-added services can be provided for government and enterprise customers, but also the pace of deploying services can be speeded up and the flexibility can be enhanced. A SDN based vCPE model was proposed and the problem of how to realize VPN services for government and enterprise customers in SDN-based vCPE networks according to their own needs was researched. Three VPN technologies of VxLAN VPN, MPLS VPN and IPSec VPN were proposed and they were compared from different perspectives. In addition, fused schemes were proposed to combine the advantages in security, transmission rate and QoS, so that government and enterprise customers can select flexible VPN products according to their own needs in bandwidth, security, delay and others.